Bioaccumulation of Hydrocarbon, Heavy Metals and Minerals in Tympanotonus Fuscatus from Coastal Region of Bayelsa State, Nigeria - Ogamba, Emmanuel N; Izah, Sylvester Chibueze; Omonibo, Erepadei (International Journal of Hydrology Research, 2016)
Tympanotonus fuscatus is found in mangrove swamps of the coastal region of the Niger Delta Nigeria. It’s a source of protein, hence is used in the preparation of delicacies. This study investigated the bioaccumulation of hydrocarbon and heavy metals and minerals in T. fuscatus var radula and T. fuscatus var fuscatus from the brackish coastal region of Bayelsa state, Nigeria. Standard analytical methods were employed. Results showed that the concentration of the metals and hydrocarbon were highest in the shell. The concentration of calcium, magnesium, nickel, cadmium, chromium, mercury and total hydrocarbon content ranged from 10.717-14.533 mg/kg, 6.447 - 8.800mg/kg, 0.048- 0.823mg/kg, 0.010 - 0.036 mg/kg, 0.020- 0.023 mg/kg, 0.001 - 0.002 mg/kg and 0.060 - 0.767 mg/kg respectively. There was a significant difference (P<0.05) in the concentration of metals and hydrocarbon between the two varieties. The concentration of cadmium and mercury were below the limit to cause diseases as reported by the World Health Organization. Similarly the concentrations of nickel, chromium and hydrocarbon in the tissue were also low. High concentration of magnesium and calcium indicated their potential for health benefits. Furthermore, the high concentration of heavy metals and hydrocarbon in the shell of both species also suggested their potentials for bioremediation for such toxicants in the aquatic ecosystem.